Sponge Art Paint sebagai Intervensi untuk Menurunkan Tingkat Kecemasan Sebelum Pemasangan Infus pada Anak Usia Prasekolah - Prawesti, Indah; Lestari, Retno; Sari, Ignasia Yunita (Jurnal Kesehatan, 2022)
Children's anxiety during the hospitalization period is caused by many things; they are in a new environment, separated from their parents, and met with health workers with various interventions such as infusion. Inserting an infusion could resulted on severe anxiety in preschoolers, and this will affect the relationship between nurses and preschoolers during the hospitalization process. In accordance with the development of cognitive and motor skills of preschoolers, one of the efforts made to reduce preschoolers' anxiety when infusions are performed is relaxation therapy. There are many forms of this therapy, and one form of which is art therapy through sponge art paint. This study aims to determine whether sponge art paint therapy influence anxiety level on preschooler before infusion installation at Panti Wilasa Citarum Hospital Semarang. This study was quantitative research method using Quasy Experimental Nonequivalent Control Group Design, and a total sampling of research were 40 respondents. The data was analyzed using Mann-Whitney U-Test statistical tests. The results showed a p-value of 0,000 (p<0,05) indicates that there is a significant diffirence in the average value of the anxiety level of preshooler before infusion installation between the control and the intervention group. It can be concluded that sponge art paint therapy influence anxiety in preshooler before infusion installation at Panti Wilasa Citarum hospital Semarang. Sponge art paint therapy research is expected to be an inspiration for nursing researchers to conduct further research to develop nursing theories, especially in sponge art paint therapy to reduce the anxiety.